Analisis Dampak Volume Produksi Home Industri Batik Gambir Tigo Sarumpun dalam Meningkatkan Kesejahteraan Tenaga Kerja Menurut Perspektif Islam - Putri Permata Sari; Yuwarman Mansyur (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
This research is based on the results of the author's observations which target that there are in IKM Batik 3 Serumpun which are trying to increase the safety of its special residents for business actors and Activity power. These rewards and bonuses are usually used by employees to meet their basic needs or their families. The level of fulfillment of these rewards and bonuses will ultimately determine the level of safety of each employee, whether the rewards can meet their needs, or vice versa. This research aims to identify the Impact of Home Batik Gambir Tigo Sarumpun Factory in increasing Safety that is in accordance with its Islamic perspective. This research is a descriptive research with a Qualitative approach. The method of collecting information used through monitoring, question and answer and selection. The method of analyzing information uses data collection, data reduction, data presentation and drawing conclusions. And the data in this research are residents who work at Home Pabrik batik Gambir togo sarumpun. The results of this research are the income of employees at Home Pabrik Batik Gambir 3 Serumpun Suka is very useful for employee safety. Sufficient income has an impact on the venting of the desires of informants (residents) or their families to continue to be fulfilled, both basic and inferior desires, as a result the safety of residents or families is assumed to continue to be good. Based on the perspective of Islamic economics, the attempted reward system is in accordance with Islamic law which suggests that the rewards received by workers are in accordance with the power that has been given.